Genealogies of shamanism : struggles for power, charisma and authority - Boekhoven, Jeroen W., 1963- (Barkhuis, 2011)
After Western-Europeans first heard the word 'shaman' in Siberia at the end of the seventeenth century, the term rapidly acquired a remarkable range of meanings in different contexts. This book traces the long genealogical journey of the notions of 'shaman' and 'shamanism'. It starts with the eighteenth-century discovery of Siberian shamans and ends with the contemporary field of shamanism in the Netherlands. By exploring the ways in which the notions came to be constructed and authorised historically, the various interpretations and conceptualisations of 'shaman' and 'shamanism' are interpreted as outcomes of struggles within distinct milieus.